Displacement sensing with two asymmetrical inclined fibers - Yang, H.Z.; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2010)
Fiber optic displacement sensor (PODS) with two asymmetrical inclined fibers is demonstrated using an intensity modulation technique. Compared to the sensor with two symmetrical inclined fibers, the sensitivities of proposed PODS are improved by 64.7%. 40.8%, and 31.8% at inclination angles of 10 degrees, 20 degrees. and 30 degrees, respectively. The analysis also shows that the increment of inclination angle increases the output sensitivity but reduces the linear range of the sensor. Compared to the case of parallel fibers, sensitivity can be improved by 3.6, 8.5, and 16 times for inclination angles of 10, 200, and 30 degrees respectively. However, the corresponding linear ranges are decreased by 67%, 55%, and 33% for inclination angles of 10, 200, and 30. respectively. (C) 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 1271-1274, 2010: Published online in Wiley Inter Science (www.interscience.wiley.com). DOI 10.1002/mop.25173